2022
DOI: 10.3389/fpubh.2022.885624
|View full text |Cite
|
Sign up to set email alerts
|

A Visualized Dynamic Prediction Model for Overall Survival in Elderly Patients With Pancreatic Cancer for Smart Medical Services

Abstract: BackgroundPancreatic cancer (PC) is a highly malignant tumor of the digestive system. The number of elderly patients with PC is increasing, and older age is related to a worse prognosis. Accurate prognostication is crucial in treatment decisions made for people diagnosed with PC. However, an accurate predictive model for the prognosis of these patients is still lacking. We aimed to construct nomograms for predicting the overall survival (OS) of elderly patients with PC.MethodsPatients with PC, older than 65 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Many studies have shown that age is an independent variable affecting OS in PDAC patients ( 26 , 33 - 35 ). Since the clinical features and prognosis of elderly PDAC patients are different from those of younger patients ( 12 , 15 , 16 ), it is not accurate to rely solely on the traditional stage systems to estimate the prognosis of these patients. In the current study, we constructed a nomogram model based on a combination of independent prognostic factors to predict survival in PDAC patients aged ≥60 years.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have shown that age is an independent variable affecting OS in PDAC patients ( 26 , 33 - 35 ). Since the clinical features and prognosis of elderly PDAC patients are different from those of younger patients ( 12 , 15 , 16 ), it is not accurate to rely solely on the traditional stage systems to estimate the prognosis of these patients. In the current study, we constructed a nomogram model based on a combination of independent prognostic factors to predict survival in PDAC patients aged ≥60 years.…”
Section: Discussionmentioning
confidence: 99%
“…Age is considered to be an independent prognostic factor for many cancers, including PC ( 12 - 14 ). Previous studies have shown that the clinical features and prognosis of elderly PC patients differ from those of younger patients ( 12 , 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations